Alignment but not Alliance: Nordic Operational Military Cooperation - Saxi, Håkon Lunde (Arctic Review on Law and Politics, 2022)
Since the start of the Ukrainian crisis in 2014, the Nordic states have sought to advance their defence cooperation “beyond peacetime” to also encompass operational military cooperation in crisis and armed conflict. Relations between the two Nordic non-NATO members, Sweden and Finland, have formed a vanguard, encompassing bilateral operational planning beyond peacetime. While no formal security policy guarantees have been exchanged, Sweden and Finland have created strong expectations that they will lend each other support in a crisis. In short, while no formal alliance treaty exists, the two states have nevertheless become closely aligned. In 2020, Sweden and Finland joined NATO member Norway in signalling their intention to strengthen their trilateral defence relationship. The following year, NATO members Norway and Denmark signed a similar agreement with Sweden. The goal of these documents was to coordinate their national operational plans – their “war plans” – and perhaps develop some common operational plans. In this article, it is argued that these agreements fall short of a formal military alliance, but that they represent an alignment policy between the Nordic states.